2008
DOI: 10.1002/btpr.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore size, shear rate, and harvest time during the constant permeate flux microfiltration of CHO cell culture supernatant

Abstract: The influence of the shear rate, the membrane pore size, and the age of the culture at time of harvest on transmembrane pressure (TMP) increase and membrane fouling during the microfiltration of a Chinese Hamster Ovary (CHO) cell culture supernatant was investigated. A hollow fiber microfiltration system operated at constant permeate flux was used. The highest TMP increase with filtration time was observed for the small membrane pore size (0.20 microm) operated at the higher shear rate (8,000 s(-1)). Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, the (anti)sticking factor for the pressure phase ( α cells_pressure‐phase ) increased by the same degree, resulting in the same net sticking factor ( α cells_net‐cycle, from Figure ) at the beginning of an experiment (i.e., where cycle‐averaged TMP is low) beginning) as at the end of an experiment (i.e., where cycle‐averaged TMP is higher). Larger pressure‐phase (anti)sticking factors, seen near the end of the experiments, correspond to an enhanced rate of removal of biological deposits from the membrane which is consistent with Stressman's observation that the removal rate of deposited biological solids from a membrane surface as a result of crossflow (during TFF) increases when there is more material deposited on the membrane. The increase in deposition rate during the exhaust cycle (i.e., α cells_exhaust‐phase ) near the end of the experiments is more difficult to explain, and might be a result of existing biological deposits on the membrane surface facilitating deposition of additional deposits.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, the (anti)sticking factor for the pressure phase ( α cells_pressure‐phase ) increased by the same degree, resulting in the same net sticking factor ( α cells_net‐cycle, from Figure ) at the beginning of an experiment (i.e., where cycle‐averaged TMP is low) beginning) as at the end of an experiment (i.e., where cycle‐averaged TMP is higher). Larger pressure‐phase (anti)sticking factors, seen near the end of the experiments, correspond to an enhanced rate of removal of biological deposits from the membrane which is consistent with Stressman's observation that the removal rate of deposited biological solids from a membrane surface as a result of crossflow (during TFF) increases when there is more material deposited on the membrane. The increase in deposition rate during the exhaust cycle (i.e., α cells_exhaust‐phase ) near the end of the experiments is more difficult to explain, and might be a result of existing biological deposits on the membrane surface facilitating deposition of additional deposits.…”
Section: Resultssupporting
confidence: 87%
“…For TFF and ATF, there is a crossflow velocity that minimizes the tendency to foul a membrane, and transmembane pressure (TMP; not Δ P ) indicates the pressure drop driving permeate flow across the membrane. Stressman and Moresoli suggested that the rate of formation of open pore area is a result of the crossflow, and correlated mathematically to a constant (that is a function of crossflow velocity) multiplied by the total amount of biomaterial currently on the membrane. Belfort and Zydney suggest that biomaterial can be “peeled off” the membrane by crossflow due to an inertial lift force which increases as the square of the tangential shear rate and the cube of the particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Reversible and irreversible fouling membrane resistances were the highest for the membrane exposed to 0.70 m·s −1 feed cross flow velocity followed by 0.22 and 0.11 m·s −1 feed cross flow rate. Stressmann and Moresoli () showed a similar trend with supernatant solution and a membrane operating under the constant flux mode. These observations may not be intuitively obvious as high shear stress applied to the liquid at the membrane surface reduces the cake layer build‐up and could be considered beneficial in reducing membrane fouling (Silva, Reeve, Husain, Rabie, & Woodhouse, ).…”
Section: Resultsmentioning
confidence: 58%
“…Previously, ATF has been modeled using a series of empirically derived equations where important parameters such as local velocity, pressure drop, and permeate flux are lumped into single average values (Kelly et al, ). The CFD approach presented in this study provided the basis for improved understanding of the impact of operating conditions on factors such as product sieving (Wang et al, ) and membrane utilization (Stressmann & Moresoli, ). A 2D axisymmetric CFD model was developed using experimental membrane resistance as an input for the simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation